Horizontal mattress uterine closure compared to single layered lock suture in cesarean section - A retrospective cohort study - Peter Khamvongsa; Chitra Gotluru; Sarah Stavros; Jordana Borges; Sabrina Bonnice (Elsevier, 2023)
Objective: The objective of this study is to compare the outcomes of standard cesarean section uterine closure, single-layered running lock sutures, versus using primary horizontal mattress sutures (the K uterine closure technique). Method: This study used a retrospective cohort chart review of patients undergoing elective primary and repeat cesarean section between January 2016 and August 2020 at a South Florida hospital. From 613 included patients, 176 received the K uterine closure technique completed by a triple board-certified physician. Remaining 437 patients received single-layered lock uterine closure completed by other physicians in the same hospital. Clinical, demographic, and post-operative outcomes were collected using patients' operative, post-operative, and progress notes. Results: Using the data gathered, the experimental group demonstrated a greater difference between pre- and post-cesarean section hemoglobin (p < 0.027) and hematocrit (p < 0.014) compared to single-layered lock closure methods. There was a significantly lower estimated blood loss (p < 0.001), however, there was no significant difference in the average quantitative blood loss (p < 0.374). There was also a significant reduction in the length of total and postoperative hospital stay (p < 0.001), but the total operation time was significantly increased (p < 0.016). No significant difference was found in the percentage of patients using opioids as pain management during hospital stay (p < 0.431). There was no need for blood transfusion nor an increase in infectious morbidity using this method. Conclusions: Using the K uterine closure technique for post-cesarean section uterine closure was a reasonable alternative for closure of hysterotomy. It led to decreased duration of hospital stay and no significant difference in quantitative blood loss. The greater difference in hemoglobin and hematocrit for the K uterine closure technique group could be explained due to the significantly greater total operation time. Although the single-layered running lock suture closure is what has been more historically performed by obstetricians for cesarean sections, this data supports the viability and efficacy of the K uterine closure technique as an equally safe, non-inferior alternative. The value of this technique for uterine closure can be confirmed with future prospective studies and potential research in reduction of uterine scar defects. Synopsis: Primary horizontal mattress closure at cesarean section provides a safe alternative to single-layered lock closure and may reduce blood loss, hospital stay, and opioid use.